COMPARISON OF THE EFFECT OF ANTIBIOTICS AND BACTERIOPHAGE PHAGE SAVB14 ON BIOFILMS FORMED BY STAPHYLOCOCCUS AUREUS VARIANT BOVIS - Горюк, Ю. В.; Кухтин, М. Д.; Горюк, В. В.; Керничний, С. П. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
During the development of mastitis in cows, the formation of a biofilm pathogen is an effective way to preserve it in the microenvironment of mammary gland. Biofilm infections are difficult to treat with antimicrobials, and bacterial resistance to antibiotics increases to 1000-fold level, compared with what is observed when grown in planktonic conditions. The aim of study – to determine and compare the effect of antimicrobial drugs and bacteriophage Phage SAvB14 in the destruction of biofilms formed by S. aureus var. bovis. Isolation and species identification of staphylococci were performed according to conventional methods using BD Baird-Parker Agar medium (HiMedia, India). Determination of ability of staphylococci to form biofilms and the number of viable bacteria was determined by the Stepanovic method. The study of sensitivity of microorganisms in biofilm form was performed on daily microbial biofilms grown in plastic Petri dishes. After 24 hours of incubation of cultures, the dishes were washed three times from planktonic (unattached) microorganisms with sterile phosphate buffer and introduced the studied antibacterial agents. After exposure, the dishes were washed three times with sterile phosphate buffer, introduced 5 cm3 of sterile 0.9% sodium chloride solution and washed the biofilm, took 1.0 cm3 of suspension, prepared a series of ten-fold dilutions, inoculated 1.0 cm3 of each dilution in Petri dishes, poured MPA and incubated at temperature of 370C for 24–48 hours to determine the number of bacteria. In determining the effect of antibiotics on bacterial biofilms, it was found that of the studied antibiotics, enrofloxacin worked best probably due to its low molecular weight and ability to penetrate the pores and channels of the biofilm to microbial cells. After the action of enrofloxacin on biofilms, staphylococcal bacteria were completely inactivated. Also, the antibiotics ceftriaxone and doxycycline were effective against bacteria in biofilms. After the action of ceftriaxone, the number of surviving bacteria was lg 1.9 ± 1.1 CFU/cm2 of biofilm area, and doxycycline lg 2.5 ± 1.2 CFU/cm2. At the same time, under the action of antibiotics penicillins, aminoglycosides and macrolides, the number of surviving microbial cells was about lg 5.3 CFU/cm2 of biofilm area. In studies on the effect of bacteriophage Phage SAvB14 on biofilms formed by S. aureus var. bovis, there was their degradation. At this, viable microbial cells from the biofilm were not isolated. In this case, we can say that the phages penetrated and reached the staphylococcal cells throughout the thickness of biofilm and bacteria were susceptible to this phage. That is, there was a passive treatment of biofilm with phages, in which lysis depended on the rate of virus uptake. Therefore, the obtained results of laboratory studies indicate the prospects of effective use of our selected specific staphylococcal bacteriophage Phage SAvB14 for the destruction of biofilm formed by S. aureus var. bovis – in mastitis of cows.